Percutaneous nephrolithotomy with multiple tracts: comparison of morbidity with singletract procedure (Bangladesh Journal of Urology, 2012)
Objective: To find out a method of percutaneous nephrolithotomy (PCNL) that can achieve greater stone clearance with acceptable morbidity. Patients and Methods: From January 2007 to May 2008, seventy patients were studied prospectively in two institutions and two other hospitals in Dhaka city for their complex renal stone management by percutaneous nephrolithotomy either with single tract or with multiple tract procedures. On the basis of assessment of calculus configuration and collecting system anatomy, patients who were managed with single tract PCNL labeled as Group A and those with multi-tract PCNL as Group B. Per-operative and post-operative events of all cases were analyzed for overall stone clearance, duration of operation time, per operative blood loss, post operative duration of haematuria, fever and analgesia requirement, urinary leakage through the nephrostomy tract, renal function and post operative hospital stay. Results: The mean stone size in Group A was 4.4(range 3.3- 6.9) cm and 5.8(range 4.1- 8.8) cm in Group B (p0.05). Urine leakage stopped earlier in group-A (24.79 ± 4.15hours) than that in Group-B (26.73 ± 4.04 hours) (p>0.05). The mean serum creatinine (mg/dL) levels preoperatively was 1.14±0.40 and 1.58±0.98; postoperatively was 1.24±0.58 and 1.91±1.64 in group A and group B respectively (p